Evaluation of the impact of the tax legislation reforms on the tax potential by fuzzy inference method - Musayev, Akif; Madatova, Shahzada; Rustamov, Samir (Elsevier, 2016)
In the paper the Mamdani-Type Fuzzy inference method is applied for the expert evaluation of the impact of the tax legislation reforms on the tax potential. The model being investigated includes 4 inputs, 8 IF-THEN rules and a single-output. Triangle, trapezoid, Gaussian and Bell-shaped membership functions are used for the fuzzification of input data and output of the system is evaluated by Gaussian curve membership function. For the investigated year the laws made reforms in the Azerbaijan tax legislation are classified and evaluated on the base of fuzzy inference system.
Keywords: Tax legislation.; Mamdani-type fuzzy approach.; Defuzzification methods.